Assessing Pre-Service Teachers’ Person-Centered Attitudes: Validity Evidence for the APBS Instrument Based on Internal Structure - Teistler Nadja (Open Education Studies, 2022)
Person-centered teacher behavior is positively related to cognitive and affective-motivational student outcomes. Although underlying teacher attitudes are thought to be of great importance for person-centered teacher-student relationships, this aspect has not been considered in empirical studies to date. This study examined the internal structure and reliability of a new self-report measure assessing attitudes on person-centered behavior toward students (APBS) in a sample of 363 German pre-service teachers aged 18-40 years (M = 22.28, SD = 3.48; 72.7% female). Exploratory factor analyses and internal consistency analyses based on polychoric correlations provided evidence for a theoretically grounded four-factor model with “unconditionality” (α = .91), “empathic understanding” (α = .92), “trust” (α =.89) and “genuineness” (α = .83) explaining 46% of the total variance. Interfactor correlations ranged between .53 and .72. There is thus preliminary evidence that the APBS test scores can be interpreted as intended. However, further validation studies are required to replicate the internal structure using confirmatory factor analyses and to examine the relations between APBS test scores and external variables. The instrument can be used in research in the field of teacher-student relationships as well as in teacher education courses addressing participants’ educational attitudes.